2013
DOI: 10.1016/j.neurobiolaging.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of medial temporal lobe atrophy for prediction of Alzheimer's disease in subjects with mild cognitive impairment

Abstract: Our aim was to compare the predictive accuracy of 4 different medial temporal lobe measurements for Alzheimer's disease (AD) in subjects with mild cognitive impairment (MCI). Manual hippocampal measurement, automated atlas-based hippocampal measurement, a visual rating scale (MTA-score), and lateral ventricle measurement were compared. Predictive accuracy for AD 2 years after baseline was assessed by receiver operating characteristics analyses with area under the curve as outcome. Annual cognitive decline was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 83 publications
5
64
0
1
Order By: Relevance
“…Our team of multi-disciplinary clinicians (HIJ, JK,öO, NR, BR) meticulously ensured the compliance of these criteria for every included SCD participants prior to classifying them as such. Prodromal AD patients had to fulfill the latest research criteria proposed by Albert et al [36], Dubois et al [37,38], and Petersen [39]: self-reported memory complaints or informed by a knowledgeable caregiver (verified during the anamnesis or using the cut-off value of ≥25 on the MAC-Q) [32] along with objective cognitive deficits (corrected for age, gender, and education) of at least 1.5 SD from the normative mean [39,40], a mini mental status examination score of ≥23 [41], and, most important, evidence of biomarkers, i.e., cerebrospinal fluid tau/A␤ 42 ratio of >0.52 [42], medial temporal lobe atrophy score ≥3 using MR imaging [43], or typical temporoparietal hypometabolism on fluorodeoxyglucose positron emission tomography (FDG-PET) imaging [36,44], but preserved activities of daily living (confirmed by a clinician during the anamnesis or by the Bayer Activities of Daily Living Scale cut-off of >5) [45]. This combination of evidence ensures the selection of patients that have the highest probability of converting to AD and are thus considered prodromal AD patients [37,38].…”
Section: Participantsmentioning
confidence: 99%
“…Our team of multi-disciplinary clinicians (HIJ, JK,öO, NR, BR) meticulously ensured the compliance of these criteria for every included SCD participants prior to classifying them as such. Prodromal AD patients had to fulfill the latest research criteria proposed by Albert et al [36], Dubois et al [37,38], and Petersen [39]: self-reported memory complaints or informed by a knowledgeable caregiver (verified during the anamnesis or using the cut-off value of ≥25 on the MAC-Q) [32] along with objective cognitive deficits (corrected for age, gender, and education) of at least 1.5 SD from the normative mean [39,40], a mini mental status examination score of ≥23 [41], and, most important, evidence of biomarkers, i.e., cerebrospinal fluid tau/A␤ 42 ratio of >0.52 [42], medial temporal lobe atrophy score ≥3 using MR imaging [43], or typical temporoparietal hypometabolism on fluorodeoxyglucose positron emission tomography (FDG-PET) imaging [36,44], but preserved activities of daily living (confirmed by a clinician during the anamnesis or by the Bayer Activities of Daily Living Scale cut-off of >5) [45]. This combination of evidence ensures the selection of patients that have the highest probability of converting to AD and are thus considered prodromal AD patients [37,38].…”
Section: Participantsmentioning
confidence: 99%
“…Analysis of three different datasets produced encouraging results [13][14][15], suggesting that the variability of cutpoints among different studies is low; however, it has been difficult to obtain data from published analyses that could be reanalyzed to confirm this finding.…”
Section: Ad Biomarkers -Csf and Imagingmentioning
confidence: 99%
“…As emerging risk factors we will test social inactivity [27], cognitive and physical inactivity [28][29][30], alcohol consumption [31], smoking [28,29] and sleep deprivation [28,29,32,33].…”
Section: Aim and Outline Of This Thesismentioning
confidence: 99%
“…The Paired Associates Learning (PAL) of the computerized CANTAB [30,31], is a visuospatial episodic memory task in which individuals were asked to pair a token with its location as follows. One or more white boxes revealed a unique token.…”
Section: Memory Testsmentioning
confidence: 99%
See 1 more Smart Citation